Pengaruh Teknik Self-Management Terhadap Perilaku Impulse Buying yang Dipicu oleh Self-Reward pada Mahasiswa Lipia Medan di Era Digital - alfin, Fitri Nurazizah; Alfin Siregar (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
The development of the digital era has led to changes in students’ consumption behavior, one of which is reflected in the increasing tendency of impulse buying, often triggered by self-reward practices. While self-reward is initially intended to enhance motivation and reduce stress, it may gradually shift into uncontrolled consumptive behavior. This study aims to examine the effect of self-management techniques implemented through group guidance services on reducing impulse buying behavior triggered by self-reward among students of LIPIA Medan. This research employed a quantitative approach using a quasi-experimental method with a one-group pretest– posttest design. The research subjects consisted of 7 students selected through purposive sampling from a population of 34 students based on high levels of impulse buying. Data were collected using an impulse buying behavior questionnaire and analyzed using the Wilcoxon Signed-Rank Test. The results indicate a significant decrease in impulse buying scores after the implementation of group guidance with self-management techniques (Z = -2.371; p = 0.018 < 0.05). These findings suggest that self-management techniques are effective in enhancing students’ self-control, increasing awareness of emotional triggers, and promoting more rational consumption behavior in the digital era.